2020
DOI: 10.2196/15052
|View full text |Cite
|
Sign up to set email alerts
|

Novel Interface Designs for Patient Monitoring Applications in Critical Care Medicine: Human Factors Review

Abstract: Background The patient monitor (PM) is one of the most commonly used medical devices in hospitals worldwide. PMs are used to monitor patients’ vital signs in a wide variety of patient care settings, especially in critical care settings, such as intensive care units. An interesting observation is that the design of PMs has not significantly changed over the past 2 decades, with the layout and structure of PMs more or less unchanged, with increm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Articles were further excluded after title, abstract, and full paper analysis by members of the multidisciplinary team (composed of engineers, health scientists, nurses, anesthesiologists, human factors specialists, and medical consultants). To ensure that all the relevant studies were identified, the team reviewed each paper’s references, looking for possible studies that were not captured with our search strategy, and 1 study was identified [ 3 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Articles were further excluded after title, abstract, and full paper analysis by members of the multidisciplinary team (composed of engineers, health scientists, nurses, anesthesiologists, human factors specialists, and medical consultants). To ensure that all the relevant studies were identified, the team reviewed each paper’s references, looking for possible studies that were not captured with our search strategy, and 1 study was identified [ 3 ].…”
Section: Methodsmentioning
confidence: 99%
“…For this task, critical care clinicians extensively use a patient monitor (PM), which is typically placed close to the patient in the intensive care unit (ICU) or operating room. The essential features of a PM used for critical care patient monitoring were presented by Andrade et al [ 3 ]. The PM uses sensors connected to the patient to measure a range of physiological signals (eg, heart rate [HR], blood pressure [BP], and saturation of peripheral oxygen [SpO 2 ]).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasingly, machines with complex control circuits are challenging human receptiveness. In intensive care medicine, the understanding of human-machine interactions is of particular importance in preventing adverse events ( 14 ). Inadequate information processing with respect to monitoring devices may contribute to individual errors leading to impaired patient outcomes.…”
Section: Introductionmentioning
confidence: 99%